Plasma lipidomic alterations during pathogenic SIV infection with and without antiretroviral therapy - Sivanandham, Sindhuja; Sivanandham, Ranjit; Xu, Cuiling; Symmonds, Jen; Sette, Paola; He, Tianyu; Funderburg, Nicholas; Abdel-Mohsen, Mohamed; Landay, Alan; Apetrei, Cristian; Pandrea, Ivona (Frontiers in Immunology, 2025)
IntroductionLipid profiles change in human immunodeficiency virus (HIV) infection and correlate with inflammation. Lipidomic alterations are impacted by multiple non-HIV-related behavioral risk factors; thus, use of animal models in which these behavioral factors are controlled may inform on the specific lipid changes induced by simian immunodeficiency virus (SIV) infection and/or antiretroviral therapy (ART).MethodsUsing ultrahigh Performance Liquid Chromatography-Tandem Mass Spectroscopy, we assessed and compared (ANOVA) longitudinal lipid changes in naïve and ART-treated SIV-infected pigtailed macaques (PTMs). Key parameters of infection (IL-6, TNFa, D-dimer, CRP and CD4+ T cell counts) were correlated (Spearman) with lipid concentrations at critical time points of infection and treatment.ResultsSphingomyelins (SM) and lactosylceramides (LCER) increased during acute infection, returning to baseline during chronic infection; Hexosylceramides (HCER) increased throughout infection, being normalized with prolonged ART; Phosphatidylinositols (PI) and lysophosphatidylcholines (LPC) decreased with SIV infection and did not return to normal with ART; Phosphatidylethanolamines (PE), lysophosphatidylethanolamines (LPE) and phosphatidylcholines (PC) were unchanged by SIV infection, yet significantly decreased throughout ART. Specific lipid species (SLS) were also substantially modified by SIV and/or ART in most lipid classes. In conclusion, using a metabolically controlled model, we identified specific lipidomics signatures of SIV infection and/or ART, some of which were similar to people living with HIV (PWH). Many SLS were identical to those involved in development of organ dysfunctions encountered in virally suppressed individuals. Lipid changes also correlated with markers of disease progression, inflammation and coagulation.DiscussionOur data suggest that lipidomic profile alterations contribute to residual systemic inflammation and comorbidities seen in HIV/SIV infections and therefore may be used as biomarkers of SIV/HIV comorbidities. Further exploration into the benefits of interventions targeting dyslipidemia is needed for the prevention HIV-related comorbidities.